Genomic Analysis of Indel and SV Reveals Functional and Adaptive Signatures in Hubei Indigenous Cattle Breeds - Liangyu Shi; Pu Zhang; Bo Yu; Lei Cheng; Sha Liu; Qing Liu; Yuan Zhou; Min Xiang; Pengju Zhao; Hongbo Chen (Animals, 2025)
The genetic diversity of cattle plays a crucial role in adapting to environmental challenges and enhancing production traits. While research has predominantly focused on single nucleotide polymorphisms (SNPs), small indel and structural variants (SVs) also significantly contribute to genetic variation. This study investigates the distribution and functional impact of insertions and deletions in five Hubei indigenous cattle breeds. A total of 3,208,816 deletions and 2,082,604 insertions were identified, with the majority found in intergenic and intronic regions. Hotspot regions enriched in immune-related genes were identified, underscoring the role of these variants in disease resistance and environmental adaptation. Our analysis revealed a strong influence of transposable elements (TEs), particularly LINEs and SINEs, on genomic rearrangements. The variants were also found to overlap with economically important traits, such as meat quality, reproduction, and immune response. Population structure analysis revealed genetic differentiation among the breeds, with Wuling cattle showing the highest differentiation. Notably, the NOTCH2 gene was identified as a candidate for regional adaptation due to its significant differentiation across populations. These findings provide valuable genomic resources for enhancing breeding programs, aiming at improving the productivity and resilience of indigenous cattle breeds in China.